Role of lifestyle interventions in reducing UTI burden among Individuals with obesity - Sourabh Sharma; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Urinary tract infections (UTIs) are a prevalent health concern globally, and their incidence is disproportionately higher among individuals with obesity. Obesity increases the likelihood of UTIs due to a range of physiological, immunological, and behavioural factors. This article explores the relationship between obesity and UTIs while emphasizing evidence-based lifestyle changes to lower this risk. The discussion includes strategies such as weight management, dietary changes, increased physical activity, proper hydration, and behavioural adjustments as vital steps for reducing UTI prevalence in obese individuals. By tackling these modifiable factors, healthcare providers can enhance UTI prevention and the overall health of this at-risk population. Keywords: Obesity, Urinary tract infections, metabolic disorders, Hygiene, Lifestyle modifications